Preparation method and application of basalt fiber coating introduced through adsorption of positive and negative charges

By introducing a multi-layer functional coating with positive and negative charge adsorption on the surface of the basalt fiber, the problem of poor compatibility between the basalt fiber and the polymer matrix is ​​solved, the interface performance and mechanical properties of the composite material are improved, and the heat resistance of the coating is improved and storage stability.

CN119191731APending Publication Date: 2024-12-27SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411368334.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The poor compatibility between basalt fibers and polymer matrix leads to the problem of low interface bonding strength and easy interface damage. The existing coatings are complex in preparation and poor temperature resistance and storage, which affects the impact of Application of materials.

Method used

The negatively charged nanoaramid coating and the positively charged ammonium (amine) cationic coating are introduced through positive and negative charge adsorption. Multiple functional coatings are formed on the surface of the basalt fibers through repeated soaking and drying steps to improve interface performance.

Benefits of technology

The interface shear strength, bending strength and mechanical properties of basalt fiber composite materials are significantly improved, the bonding between fiber and matrix is ​​improved, and the heat resistance and storage stability of the coating are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191731A_ABST
    Figure CN119191731A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a basalt fiber coating introduced through adsorption of positive and negative charges, and relates to the technical field of preparation of basalt fiber coatings. The BF coating provided by the invention comprises the following steps: step 1, soaking BF in a Piranha solution, washing and drying; step 2, soaking in an ammonium (amine) cationic modifier solution, taking out and drying; 3, soaking the BF fiber in an aramid nanofiber (ANF) solution, taking out the BF fiber, and drying the BF fiber to obtain a first cation / ANF coating layer; and step 4, repeating the treatment operation to obtain the BF of which the surface is introduced with the multi-layer functional cation / ANF coating. The cation / ANF layer is introduced, so that the thickness of an interface transition area is increased, the elasticity modulus has a better transition effect, the overall failure of the composite material is delayed by reducing stress concentration, the interface performance of BF is improved, and the mechanical property of the BF composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of basalt coating preparation, and in particular to a preparation method and application of a basalt fiber coating introduced through positive and negative charge adsorption. Technical Background

[0002] Basalt fiber is a kind of fiber made by melting natural basalt ore and spinning. Due to its excellent properties such as high strength, high modulus, high and low temperature resistance, corrosion resistance, and electrical insulation, basalt fiber composite materials have been further promoted and applied in the fields of automobile transportation, new energy, power chemical industry, etc. With the continuous development and progress of the economy and society, especially with the popularity of concepts such as energy conservation and emission reduction, green environmental protection, etc., functional composite materials with the main goal of exerting the physical and chemical properties of materials are receiving more and more attention.

[0003] The poor compatibility of basalt fiber and polymer matrix leads to many defects and deficiencies in basalt fiber reinforced resin-based composite materials, such as low interfacial bonding strength and easy destruction of the interfacial phase. Among them, fiber coating is one of the methods to solve this key problem. Basalt fiber coating is mainly epoxy resin, which is mostly derived from the traditional formula of glass fiber coating. However, this type of coating often causes mismatch between basalt fiber and matrix, which becomes one of the bottlenecks restricting the application and development of basalt fiber reinforced resin-based composite materials. Therefore, it is of great significance to vigorously strengthen the application and development of basalt fiber coating.

[0004] At present, the research on basalt coatings includes epoxy resins and phenolphthalein polyarylethersulfone resins. For example, patent CN113003948B discloses a basalt coating, which is a phenolphthalein polyarylethersulfone resin with fumed silica, emulsifier, coupling agent, organic solvent, and water, so that the resulting coating has excellent heat resistance and good storage stability; patent CN109761510A patent application discloses a basalt fiber impregnation agent, which is a film-forming agent, a lubricant, an antistatic agent, etc., and the impregnation agent can improve the basalt fiber bundling and wear resistance, thereby improving the tensile properties of the basalt fiber. However, the above-mentioned coating is complicated to prepare and difficult to apply in practice. The above-mentioned impregnation agent has poor temperature resistance and storage performance, and has poor bonding performance between basalt fiber and resin composite materials. Therefore, it is very important to provide a new basalt fiber coating, which can simultaneously improve the interfacial shear strength, interlaminar shear strength, bending strength of basalt fiber composite materials, and improve the interfacial properties of basalt fibers. Summary of the invention

[0005] The main purpose of the present invention is to provide a preparation method and application of a basalt fiber coating introduced by positive and negative charge adsorption, which can improve interface performance and enhance interlaminar shear strength and bending strength of basalt fiber composite materials.

[0006] In one aspect of the present invention, the present invention provides a method for preparing a basalt fiber coating. According to an embodiment of the present invention, the basalt fiber coating comprises a negatively charged nano-aramid coating and a positively charged ammonium (amine) cationic coating, and the polar group and the aramid are connected by positive and negative charge adsorption.

[0007] The following steps are involved:

[0008] A) basalt fiber (BF) is soaked in a Piranha solution, washed with deionized water, and then soaked in an ammonium (amine) cationic modifier solution, taken out and dried to obtain a basalt fiber with a first layer of cationic coating;

[0009] B) immersing the basalt fiber with the first layer of cationic coating in an aramid nanofiber (ANF) solution, taking it out, repeatedly washing it with deionized water, and drying it to obtain a basalt fiber with a double layer of cationic / ANF coating;

[0010] C) immersing the basalt fiber with the first layer of ANF coating adsorbed with positive and negative charges in an ammonium (amine) cationic modifier solution, repeating the operation in A), taking out and drying to obtain the basalt fiber with the second layer of cationic coating;

[0011] D) immersing the basalt fiber with the second layer of cationic coating in the aramid nanofiber (ANF) solution again, repeating the operation of B), taking it out, repeatedly washing it with deionized water, and drying it to obtain two double-layer cationic / ANF coated basalt fibers;

[0012] E) Repeat the above C) and D) operations, and immerse repeatedly in this order to perform positive and negative charge adsorption. Through this positive and negative charge adsorption effect, a multi-layer functional coating of positive and negative charge adsorption is introduced on the surface of the basalt fiber, and the coating thickness is about (400-2000) nm.

[0013] Preferably, the preparation method of the Piranha solution in step A) is: uniformly mixing (95-98)% by mass of concentrated sulfuric acid and (10-30)% by mass of concentrated hydrogen peroxide solution in a volume ratio of 3:1 to obtain the Piranha solution;

[0014] Preferably, the preparation method of the ammonium (amine) cation modifier solution in step A) is: adding the ammonium (amine) cation modifier into deionized water, and adjusting the mass concentration of the ammonium (amine) cation modifier solution to (1.0-5.0)%.

[0015] The cationic modifier is selected from one or more of polydiallyldimethylammonium chloride, quaternary ammonium salt, and polyethylene polyamine.

[0016] Preferably, a polydiallyldimethylammonium chloride cationic modifier solution.

[0017] Preferably, the immersion time in the Piranha solution is (1-2) h, the immersion time in the ammonium (amine) cation modifier solution is (15-30) min, the drying temperature is (105-115) ° C, and the drying and heat preservation time is (15-30) min.

[0018] The ANF solution in step B) is prepared by mixing the aramid fiber with the sizing agent removed, an inorganic base, a co-solvent and an organic solvent to form an intermediate mixture, which is stirred and mixed under closed conditions to obtain a transparent and clear ANF solution.

[0019] Preferably, the composition (mass fraction) of the ANF solution is:

[0020] Aramid fiber (0.20% to 2%): inorganic base (0.32% to 1%): co-solvent (2.00% to 3%): organic solvent (88.00% to 96.7%).

[0021] The aramid fiber is one or more of meta-aramid nanofibers, para-aramid nanofibers and heterocyclic aramid (aramid III) nanofiber solutions.

[0022] Preferably, heterocyclic aramid (aramid III) nanofiber solution.

[0023] The inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and slaked lime.

[0024] The co-solvent is selected from one or more of water, methanol, ethanol and ether.

[0025] The organic solvent includes one or more of dimethyl sulfoxide and dimethylacetamide.

[0026] Preferably, the intermediate material mixture is stirred and mixed under closed conditions for (24-48) hours at a stirring speed of (700-1000) r / min to obtain a transparent and clear ANF solution.

[0027] Preferably, the soaking time in step B) is (15-30) min, the mixture is repeatedly washed with deionized water until the pH value is (8-9), the drying temperature is (105-115)° C., and the drying and heat preservation time is (15-30) min.

[0028] In another aspect of the present invention, the present invention provides a basalt fiber composite material. According to an embodiment of the present invention, the basalt fiber composite material comprises: the basalt fiber with the positive and negative charge adsorbed multi-layer functional coating as described above, a base resin such as an epoxy matrix or a thermoplastic matrix, the basalt fiber and the base resin are alternately and directionally laid in a certain proportion, hot-pressed in a flat vulcanizer according to a curing system, and naturally cooled to room temperature in the air, and finally a basalt fiber composite material is obtained.

[0029] In the above preparation method, the surface roughness and surface energy of the basalt fiber after single-layer or multi-layer cationic / ANF coating are increased, and the nano-aramid in the coating surface is also embedded in the matrix, and the discrete interfacial interlayer region becomes a hierarchical nanostructure, thereby bridging the discontinuity and delaying the interlayer damage by improving the load transfer mechanism between the fiber and the matrix. In addition, the nano-aramid around the interface layer enhances the toughness of the epoxy matrix, and the addition of the two effects leads to the improvement of the interfacial bonding strength. At the same time, the charge interaction between the positively charged fiber surface and the negatively charged nano-aramid produces a more tightly packed nanostructured interface and improves the adhesion to the fiber surface. As a result, the basalt fiber composite material has excellent mechanical properties such as interface performance, bending strength and interlaminar shear strength, which will not be described in detail here.

[0030] The mass ratio of the basalt fiber to the base resin in the step is 2:1.

[0031] The base resin is one or more of an epoxy matrix and a thermoplastic matrix (polyarylethernitrileketone resin, polyaryletherketone resin or polyarylethersulfone resin) film.

[0032] Preferably, the epoxy matrix is ​​the base resin.

[0033] The layering method is [0] 6s .

[0034] The curing system is:

[0035] ① Epoxy matrix: The epoxy matrix is ​​composed of 10 parts of epoxy resin and 8 parts of methyltetrahydrophthalic anhydride. The temperature is raised to 150°C and kept for 1 hour on a flat vulcanizer, and the pressure is increased to 3MPa, and the temperature and pressure are kept at 150°C and 3MPa for 3 hours, and finally cooled naturally to room temperature in the air.

[0036] ② Thermoplastic matrix: Heat to (280-390)℃ on a flat vulcanizer and keep warm for 2h, pressurize to 5MPa, maintain constant temperature and pressure for 1h, and finally cool naturally to room temperature in the air. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0038] Figure 1 Schematic diagram of the principle of positive and negative charge adsorption of cations / ANF coating;

[0039] Figure 2 (a) Scanning electron microscopy (SEM) image of uncoated BF.

[0040] Figure 2 (b) SEM image of BF with positive and negative charge adsorption cation layer;

[0041] Figure 2 (c) and Figure 2 (d) SEM image of positive and negative charge adsorption of ANF-cation layer-BF;

[0042] Figure 3 (a) Size of the material transition zone of the uncoated BFRP interface (atomic force microscopy AFM photo);

[0043] Figure 3 (b) Interface transition zone size of BFRP material containing one double-layer cation / ANF coating (AFM photo); Specific implementation plan

[0044] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0045] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0046] The present invention provides a basalt fiber coating, which comprises the following components by weight ratio:

[0047] Aramid fiber 0.20%~2.00%

[0048] Inorganic alkali 0.32%~1.00%

[0049] Solvent 2.0%~3.0%

[0050] Organic solvent 88.0%~96.7%

[0051] The basalt coating provided by the present invention adopts aramid fiber, and is matched with an organic solvent, a cosolvent, a cationic modifier, and an inorganic base to obtain the cationic / ANF coating on the surface of the basalt fiber.

[0052] The use of the above-mentioned aramid fiber as the main component to form a basalt fiber coating can increase the surface roughness and surface energy of the coated basalt fiber. In the composite material, the nano-aramid on the coating surface is embedded in the matrix, and the discrete interlayer region becomes a hierarchical nanostructure, thereby bridging the discontinuity and delaying interlayer damage by improving the load transfer mechanism between the fiber and the matrix. In addition, the nano-aramid around the interface enhances the toughness of the epoxy matrix. The addition of the two effects leads to an improvement in the interlayer shear strength. At the same time, the electrostatic interaction between the positively charged fiber surface and the negatively charged nano-aramid produces a more densely packed nanostructure interface and improves the adhesion to the fiber surface.

[0053] The aramid fiber of the present invention has no special source restriction. The aramid nanofiber is aramid fiber or aramid liquid crystal processed by technical means to make its diameter reach more than ten microns. Nano-aramid and aramid fiber have the same structure, and at the same time, due to the presence of carboxyl and amine functional groups in nano-aramid, it has a stronger active surface. Nano-aramid has the advantages of large specific surface area, high aspect ratio, excellent strength, modulus and high temperature resistance.

[0054] The aramid fiber used in the present invention is used to prepare aramid nanofibers. The inorganic base accounts for 0.32% to 1.00% by weight in the coating. The present invention has no limitation on the source of the inorganic base. The inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and slaked lime.

[0055] In the present invention, the coating further contains a cosolvent. The water is preferably one or more of water, methanol, ethanol, and ether. The mass ratio of the cosolvent in the coating is 2.0% to 3.0%.

[0056] In the present invention, the organic solvent is preferably one or more of dimethyl sulfoxide and dimethylacetamide, accounting for 88.0% to 96.7% by weight in the coating.

[0057] The present invention also provides a method for preparing the basalt fiber coating described in the above technical solution, comprising the following steps:

[0058] a) The aramid fiber is washed in acetone to remove the sizing agent on the fiber surface, and then the aramid fiber is completely washed with a co-solvent and dried in a vacuum oven.

[0059] b) The cleaned and dried aramid is cut into short fibers, and then aramid fibers, inorganic alkali and organic solvent are added to a flask in sequence to obtain an intermediate material.

[0060] c) stirring and mixing the above mixture under closed conditions to obtain a nano-aramid solution.

[0061] d) The basalt fiber is first treated with Piranha solution, soaked for a certain period of time, repeatedly washed with deionized water to a certain thickness, and dried.

[0062] e) treating the basalt fiber treated with the Piranha solution in a cationic modifier solution, soaking for a certain period of time, repeatedly washing with deionized water to a certain temperature, and drying.

[0063] f) placing the modified basalt fiber in a nano-aramid ANF solution to obtain a basalt fiber cationic / ANF coating through positive and negative charge adsorption.

[0064] g) By alternately repeating e) and f), a multi-layer basalt fiber cationic / ANF coating can be obtained.

[0065] In the present invention, in the step a), the condensation reflux can be carried out in a Soxhlet extractor without any special requirements, and can be obtained by a preparation method well known to those skilled in the art.

[0066] In the present invention, there is no particular limitation on the mixing method in step b), as long as the components can be mixed evenly.

[0067] In the present invention, in the step c), the stirring speed is preferably 800 rpm. The temperature is room temperature. The stirring speed and temperature are conducive to uniform dispersion of the nano-aramid fiber, and the stirring time is (24 to 48) hours. After the stirring, a nano-aramid fiber solution is obtained.

[0068] In the present invention, in the steps d) and e), the preparation method of the Piranha solution is: (95-98)% by mass of concentrated sulfuric acid and (10-30)% by mass of concentrated hydrogen peroxide solution are uniformly mixed in a volume ratio of 3:1 to obtain the Piranha solution.

[0069] The preparation method of the ammonium (amine) cation modifier solution in the step is: adding the ammonium (amine) cation modifier into deionized water, and adjusting the mass concentration of the ammonium (amine) cation modifier solution to (1.0-5.0)%.

[0070] In the present invention, the cationic modifier is selected from one or more of polydiallyldimethylammonium chloride, quaternary ammonium salt, and polyethylene polyamine.

[0071] The treatment method is as follows: soaking in Piranha solution for (1-2) hours, soaking in cationic modified solution for (15-30) minutes, soaking in ANF solution for (15-30) minutes, taking out and repeatedly washing with deionized water until the pH value is (8-9), drying at (105-115)°C, and drying and heat preservation time for (15-30) minutes.

[0072] The present invention also provides a basalt fiber composite material, comprising: coated basalt fiber and matrix resin; wherein the coating used for the coated basalt fiber is the basalt fiber coating described in any one of the above technical solutions or the basalt fiber coating prepared by the preparation method described in any one of the above technical solutions.

[0073] Due to the above scheme, the present invention uses positive and negative charge adsorption to introduce a single or multi-layer cationic / ANF coating technology on the surface of basalt fiber, which has the following advantages:

[0074] 1) The present invention is used to perform cationic / ANF coating treatment on the surface of basalt fiber, which can improve its surface properties, increase the wetting speed with the matrix resin, and improve the wetting effect, which provides a strong guarantee for forming a high-quality interface structure.

[0075] 2) The multifunctional cationic / ANF coating treatment on the surface of basalt fiber can optimize the fiber body performance to a certain extent and improve the tensile strength performance of the fiber body.

[0076] 3) Cationic / ANF coating treatment on the surface of basalt fiber can improve the interfacial bonding strength of basalt fiber composites, while also improving mechanical properties such as flexural strength and interlaminar shear strength.

[0077] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0078] Example 1

[0079] Preparation of coating

[0080] Raw materials: cationic modifier (polydiallyl dimethyl ammonium chloride) 0.78%, aramid III fiber 0.20%, inorganic base 0.32%, cosolvent 2.00%, organic solvent 96.7%.

[0081] preparation:

[0082] The aramid III fiber was washed in condensed refluxed acetone at 60°C for 24 hours to remove the coating on the fiber surface, and then the aramid III was completely washed with a co-solvent and dried in a vacuum oven at 80°C for 12 hours.

[0083] The cleaned and dried aramid III is cut into short fibers, and then aramid III fibers, inorganic base potassium hydroxide, co-solvent, and finally organic solvent dimethyl sulfoxide are added to the flask in sequence, and the mixture is stirred and mixed under closed conditions for 24 hours to obtain a deep red nano-aramid ANF solution.

[0084] First, the basalt fiber is immersed in the Piranha solution for 1.5 hours, then washed with deionized water to a pH of 8, and kept at 110°C for 25 minutes. Then, it is immersed in a polydiallyldimethylammonium chloride cationic modifier solution for 20 minutes, washed with deionized water to a pH of 8, and kept at 110°C for 25 minutes. The modified basalt fiber is then placed in a nano-aramid ANF solution and immersed for 30 minutes. Through alternating adsorption of positive and negative charges, a single-layer or multi-layer cationic / ANF coating of the basalt fiber is obtained.

[0085] At the same time, prepare the composite material. First, mix 10 parts of epoxy resin and 8 parts of methyltetrahydrophthalic anhydride evenly, heat and degas in a 70℃ oven for 30 minutes, then take 36 parts of modified basalt fiber and the mixed resin in an alternating layer forming method, and use a flat vulcanizer to cure and form in a mold with a size of 1900*300*2mm. The mold is coated with a release agent in advance. Molding steps: heat the prepared template to 150℃ on the vulcanizer for 1h, pressurize to 3MPa, maintain a constant temperature and pressure of 150℃ and 3MPa for 3h, and remove the template for demolding after cooling.

[0086] Figure 2 The SEM morphology of the basalt fiber surface after coating with polydiallyldimethylammonium chloride solution and immersion coating with nano-aramid slurry. Initially, the surface of the cleaned and untreated basalt fiber is smooth, and there is almost no chance of mechanical interlocking between the fiber and the resin, which results in the interfacial adhesion mainly relying on the chemical bonds and compatibility between the fiber and the matrix. Figure 2 Compared with the unmodified fiber in (a), Figure 2 (b) Example 1: It can be observed that the surface of the fiber becomes rougher and more uneven after being coated with polydiallyldimethylammonium chloride solution and immersed in nano-aramid slurry, and there are lamellar flakes adhering to the surface of the fiber. Figure 2(c)(d) In Examples 2 and 3, it can be clearly observed that the nano-aramid on the fiber surface is adsorbed on the fiber surface. Since the nano-aramid coating has a rather rough surface morphology and maintains a nanoscale thickness, the mechanical engagement between the fiber and the matrix is ​​enhanced. The presence of the coating covers the defects on the fiber surface, and the good mechanical properties of the nano-aramid can strengthen the interface between the fiber and the resin, which has a positive effect on the mechanical properties of the composite material.

[0087] Figure 3 This is an AFM image of the interfacial elastic modulus transition zone of the BF fiber composite material modified by the positive and negative charge adsorption single-layer cation / ANF coating. AFM force probe test shows that the interface transition zone size of the original uncoated BF fiber composite material is 667nm, and the interface transition zone width of the BFRP material using a single layer of cation / ANF is increased to 1022nm, which indicates that the single layer of cation / ANF increases the thickness of the interface transition zone, allowing a better transition of the elastic modulus, and delaying the overall failure behavior of the composite material by reducing stress concentration.

[0088] Performance Testing

[0089] The performance of the basalt fiber and its composite material obtained in the above experiment was tested. The contact angle between the basalt fiber modified by the cationic / ANF coating of the present invention and the resin was 49.2°, the interface shear strength was 83.3MPa, and the interlaminar shear strength reached 88.1MPa. The flexural strength of the basalt fiber composite material reached 1685.9MPa.

[0090] Example 2

[0091] Raw materials: para-aramid fiber 1.00%, inorganic base 0.80%, cosolvent 2.6%, cationic modifier 2.50%, organic solvent 93.1%.

[0092] Preparation: Prepare according to the preparation method of Example 1 and the raw material ratio of Example 2.

[0093] The obtained coated basalt fiber and its composite material were tested according to the test method of Example 1. The results showed that the obtained contact angle was 48.3°, the interface shear strength was 81.9 MPa, the interlaminar shear strength reached 82.3 MPa, and the flexural strength of the basalt fiber composite material reached 1685.1 MPa.

[0094] Example 3

[0095] Raw materials: meta-aramid fiber 2.00%, inorganic base 1.00%, cosolvent 3.0%, cationic modifier 5.00%, organic solvent 88.0%.

[0096] Preparation: Prepare according to the preparation method of Example 1 and the raw material ratio of Example 3.

[0097] The obtained coated basalt fiber and its composite material were tested according to the testing method of Example 1. The results showed that the obtained contact angle was 50.5°, the interface shear strength of the basalt fiber composite material was 84.2 MPa, the interlaminar shear strength reached 86.8 MPa, and the bending strength of the basalt fiber composite material / epoxy reached 1687.9 MPa.

[0098] Comparative Example 1

[0099] The performance of the uncoated basalt fiber and its composite material was tested according to the test process of the above example. The results showed that the contact angle was 44.3°, the interface shear strength was 65.1MPa, and the interlaminar shear strength reached 63.2MPa. The flexural strength of the basalt fiber composite material reached 1294.4MPa.

[0100] From the test results of Examples 1 to 3 and Comparative Example 1, it can be seen that the cationic / ANF coating provided by the present invention can effectively improve the interface shear strength, interlaminar shear strength and flexural strength. The interface shear strength of the BF composite material in Example 3 is improved by 29.3%, the interlaminar shear strength is improved by 35.3%, and the flexural strength of the composite material is improved by 30.4%. The cationic / ANF coating provided by the present invention can effectively improve the bonding between basalt fiber and matrix resin and provide good mechanical properties.

[0101] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A preparation method and application of a basalt fiber coating introduced by positive and negative charge adsorption, comprising the following steps: A) After soaking basalt fiber (BF) in Piranha solution for (1-2) hours, it is washed with deionized water, and then soaked in ammonium (amine) cationic modifier solution, and then taken out and dried to obtain basalt fiber with a first layer of cationic coating; B) immersing the basalt fiber with the first layer of cationic coating in an aramid nanofiber (ANF) solution, taking it out, repeatedly washing it with deionized water, and drying it to obtain a basalt fiber with a double layer of cationic / ANF coating; C) immersing the basalt fiber with the first layer of ANF coating adsorbed with positive and negative charges in an ammonium (amine) cationic modifier solution, repeating the operation in A), taking out and drying to obtain the basalt fiber with the second layer of cationic coating; D) immersing the basalt fiber with the second layer of cationic coating in the aramid nanofiber (ANF) solution again, repeating the operation of B), taking it out, repeatedly washing it with deionized water, and drying it to obtain two double-layer cationic / ANF coated basalt fibers; E) Repeat the above C) and D) operations, and immerse repeatedly in this order to perform positive and negative charge adsorption. Through this positive and negative charge adsorption effect, a multi-layer functional coating of positive and negative charge adsorption is introduced on the surface of the basalt fiber, and the coating thickness is about (400-2000) nm.

2. The preparation method according to claim 1, characterized in that: The Piranha solution in step A) is prepared by mixing (95-98)% by mass of concentrated sulfuric acid and (10-30)% by mass of concentrated hydrogen peroxide solution in a volume ratio of 3:1; the ammonium (amine) cationic modifier solution in step A) is one or more of polydiallyldimethylammonium chloride, quaternary ammonium salt, and polyethylene polyamine.

3. The preparation method according to claim 2, characterized in that: Add the ammonium (amine) cation modifier into deionized water and adjust the mass concentration of the ammonium (amine) cation modifier solution to (1.0-5.0)%.

4. The preparation method according to claim 1, characterized in that: The soaking time of step A) is (1-2) hours, the drying temperature is (105-115)°C, and the drying and heat preservation time is (15-30) minutes.

5. The preparation method according to claim 1, characterized in that: The ANF solution in step B) is one or more of meta-aramid nanofiber, para-aramid nanofiber and heterocyclic aramid (aramid III) nanofiber solutions.

6. The preparation method according to claim 5, characterized in that: The ANF solution preparation comprises the following steps: ① Wash the aramid fiber in acetone to remove the sizing agent on the fiber surface, then use a co-solvent to completely wash the aramid fiber and dry it in a vacuum oven; ② The cleaned and dried aramid is cut into short fibers, and then aramid fibers, inorganic alkali, co-solvent and organic solvent are added to the flask in sequence to obtain an intermediate material mixture; ③ The intermediate material mixture is stirred and mixed under closed conditions for (24-48) hours at a stirring speed of (700-1000) r / min to obtain a transparent ANF solution.

7. The preparation method according to claim 6, characterized in that: The composition (mass fraction) of the ANF solution is: aramid fiber (0.20% to 2%): inorganic base (0.32% to 1%): cosolvent (2.00% to 3%): organic solvent (88.00% to 96.7%); The inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide and slaked lime; The co-solvent is selected from one or more of water, methanol, ethanol and ether; The organic solvent includes one or more of dimethyl sulfoxide and dimethylacetamide.

8. The preparation method according to claim 1, characterized in that: The soaking time of step B) is (15-30) min, and the mixture is repeatedly washed with deionized water until the pH value is (8-9). The drying temperature is (105-115)° C., and the drying and heat preservation time is (15-30) min.

9. An application of the positive and negative charge adsorption coated basalt fiber according to any one of claims 1 to 8 in the field of composite materials, characterized in that: The following steps are involved: Take 20 parts of basalt fibers with positive and negative charge adsorption coatings and 10 parts of base resin films and lay them alternately and mix them evenly; the base resin is one or more of epoxy matrix and thermoplastic matrix (polyarylether nitrile ketone resin, polyarylether ketone resin or polyarylether sulfone resin) films; The layering method is [0] 6s , laid alternately and directional on the mold; Use a flat vulcanizing machine to heat and press to shape under a certain curing system; The mixture was naturally cooled to room temperature in air to obtain a basalt fiber composite material.

10. An application of the positive and negative charge adsorption coated basalt fiber according to any one of claims 1 to 8 in the field of composite materials, characterized in that: The curing system is: Epoxy matrix: heated to 150°C and kept warm for 1 hour on a flat vulcanizer, pressurized to 3MPa, maintained at 150°C and 3MPa for 3 hours, and finally cooled naturally to room temperature in the air; the epoxy matrix is ​​composed of 10 parts of epoxy resin and 8 parts of methyltetrahydrophthalic anhydride; thermoplastic matrix: heated to (280-390)°C and kept warm for 2 hours on a flat vulcanizer, pressurized to 5MPa, maintained at a constant temperature and pressure for 1 hour, and finally cooled naturally to room temperature in the air.

Citation Information

Cited By

  • Composite wire rod and 3D printing product made of composite wire rod

    CN121950006A